2015
DOI: 10.3133/sir20105090u
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of undiscovered copper resources associated with the Permian Kupferschiefer, Southern Permian Basin, Europe

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Previous age determinations of the Kupferschiefer mineralization have tended to produce one limited age range and postulate one phase of mineralization for each sample suite and it is only recently that models for Kupferschiefer mineralization have incorporated the full spectrum of published ages (e.g., Zientek et al, 2015). The current study is realistically the first to generate a range of ages using one technique and for material collected in close proximity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous age determinations of the Kupferschiefer mineralization have tended to produce one limited age range and postulate one phase of mineralization for each sample suite and it is only recently that models for Kupferschiefer mineralization have incorporated the full spectrum of published ages (e.g., Zientek et al, 2015). The current study is realistically the first to generate a range of ages using one technique and for material collected in close proximity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsidence rates were not constant and periods when subsidence and heat flow increased could have led to specific episodes of increased fluid release and mineralization. Zientek et al (2015) illustrated the association between basin development and periods of mineralization, and this approach has been adopted and extended here, with the addition of further age determinations and taking into account Previous attempts to quantify the volumes of fluid involved in the Kupferschiefer mineralization have advocated the presence of relatively high concentrations of copper in the hydrothermal fluids (e.g., 1000 ppm; Jowett, 1986;127 ppm;Cathles et al, 1993;60 ppm;Blundell et al, 2003), values not readily found elsewhere in fluids from similar, low-temperature sedimentary basin environments (e.g. Sverjensky, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations